De la nécessité pour les femmes chirurgiens de « faire leurs preuves » - Emmanuelle Zolesio (Université de Provence, 2011)
The purpose of this paper is to underline the remaining obstacles to the feminization of surgery. An ethnographic study shows that, although the feminization of medicine as a whole is real, surgery remains the most under-feminized area of medical specialization and sexist behaviors from senior surgeons are partly responsible for this situation. In fact, female students in surgery are always suspected of being less involved in their jobs as they are potential mothers, they are discredited in advance in matters of physical capacities, and are considered as too weak emotionally to "cope" in this difficult profession.